Dimensions of emotional intelligence related to physical and mental health and to health behaviors - Fernández-Abascal, Enrique G.; Martín-Díaz, María Dolores (Frontiers in Psychology, 2015)
In this paper the relationship between Emotional Intelligence and health is examined. The current work investigated the dimensions of EI are sufficient to explain various components of physical and mental health, and various categories of health-related behaviors. A sample of 855 participants completed two measures of EI, the Trait Meta-Mood Scale (TMMS) and Trait Emotional Intelligence Questionnaire (TEIQue), a measure of health, the Health Survey SF-36 Questionnaire (SF-36); and a measure of health-related behaviors, the Health Behavior Checklist (HBC). The results show that the EI dimensions analyzed are better predictors of mental health than of physical health. The EI dimensions that positively explain the Mental Health Component are Well-Being, Self-Control and Sociability, and negatively, Attention. Well-Being, Self-Control and Sociability positively explain the Physical Health Component. EI dimensions predict a lower percentage of health-related behaviors than they do health components. Emotionality and Repair predict the Preventive Health Behavior category, and only one dimension, Self-Control, predicts the Risk Taking Behavior category. Older people carry out more preventive behaviors for health.